2009
DOI: 10.1111/j.1601-5223.1972.tb01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic properties in populations of hexaploid Phleum pratense

Abstract: The meiotic properties were studied in two Norwegian populations of Phleum pratense L. (Grindstad and Bodin), one Danish (Pajbjerg) and one Russian population (Rjadovaja). At diakinesis, multivalents in addition to bivalents were found in most of the sporocytes examined, and the mean frequency per sporocyte ranged from 1.09 in Bodin to 1.39 in Grindstad. The differences between populations were not statistically significant. First metaphase was unsuitable for determination of bivalents and multivalents because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Additionally, four primer combinations from Saltonstall (2001) were screened (trnCF:rpoB, psaI:rbcL, trnS:psbD, and psaA:orf170). The exact segregation pattern of the hexaploid P. pratense is not known, but studies indicate a complex inheritance pattern, and it has not been possible to confirm neither a strict disomic nor polysomic inheritance (see e.g., Nordenskiöld, 1945;Simonsen, 1972). Nested primers exactly the number of homologous alleles at a locus.…”
Section: Chloroplast Dna Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, four primer combinations from Saltonstall (2001) were screened (trnCF:rpoB, psaI:rbcL, trnS:psbD, and psaA:orf170). The exact segregation pattern of the hexaploid P. pratense is not known, but studies indicate a complex inheritance pattern, and it has not been possible to confirm neither a strict disomic nor polysomic inheritance (see e.g., Nordenskiöld, 1945;Simonsen, 1972). Nested primers exactly the number of homologous alleles at a locus.…”
Section: Chloroplast Dna Analysesmentioning
confidence: 99%
“…However, it was widespread in all parts of Norway 150 yr ago (Blytt, 1876), so at least one can say that it is naturalized in this region. In addition to its complex inheritance patterns (see e.g., Nordenskiöld, 1945;Simonsen, 1972), one of the hypotheses is that the Nordic timothy is devoid of genetic diversity. However, progress in breeding timothy has been slow in the Nordic region, and the most widespread Nordic cultivar (Grindstad) is still a landrace originating from a farm in the southeastern part of Norway (Opsahl, 1964;Tamaki et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The plants of S. impressa with chromosome rearrangement manifest considerable sterility, amounting to nearly 50 per cent. The deleterious effect of univalents on pollen stainability observed in S. impressa has been documented by Simonsen (1972) in Phleum pratense, and by Fiona et al (1988) in Solanum muricatum. However, Dnyansagar and Sudhakaran (1970) in Vinca rosea, Merker (1971) in Triticale, Gatt et al (2000) in some hybrids of Dahlia, and Palma-Silva et al (2004) in Vriesea and Aechmea demonstrated that the frequency of univalents is not correlated with pollen stainability.…”
Section: Discussionmentioning
confidence: 92%
“…The deleterious effect of univalents on pollen stainability has been documented by Simonsen (1972) in Phleum pratense, and by Fiona et al (1988) in Solanum muricatum, while other authors showed that the frequency of univalents is not correlated with pollen stainability. Such studies include those by Dnyansagar and Sudhakaran (1970) in Vinca rosea, Merker (1971) in Triticale, Gatt et al (2000) in some hybrids of Dahlia, and Palma-Silva et al (2004) in Vriesea and Aechmea.…”
Section: Introductionmentioning
confidence: 93%